Sınır aşan şirket birleşmelerine uygulanacak hukuk - Kavlak, Bengül (Dokuz Eylül Üniversitesi, 2017)
Son yıllarda, uluslararası ticaret hukukundaki gelişmelerle birlikte sınır aşan şirket birleşmeleri de giderek önem kazanmıştır. Şirketler bakımından yabancı bir şirketle birleşmenin getirdiği pek çok avantaj yanında, çeşitli zorluklar da mevcuttur. Bu zorluklardan en önemlilerinden bir tanesini de sınır aşan birleşmelere uygulanacak hukukun tespiti oluşturmaktadır. AB hukukunda, sınır aşan şirket birleşmelerine ilişkin düzenlemeler öngörülerek üye devletler arasındaki uygulamanın yeknesaklaştırılması adına 2005/56/EC sayılı Direktif kabul edilmiştir. Türk hukuku bakımından ise, sınır aşan şirket birleşmelerinin önemine vurgu yapılmakla birlikte bu hususta henüz bir düzenleme getirilmiş değildir. Çalışmada, AB hukukunda bu hususta öngörülen düzenlemeler de değerlendirilmek suretiyle, Türk hukukunda sınır aşan şirket birleşmelerine uygulanacak hukukun tespiti üzerinde durulmuştur. Sınır aşan şirket birleşmelerine uygulanacak hukuka ilişkin görüşler de değerlendirilerek, AB hukuku ile de uyum sağlamak adına, Türk hukukunda her bir birleşme işlemi için uygulanacak hukuk değerlendirilmiş ve sınır aşan şirket birleşmelerine uygulanacak hukuka ilişkin düzenleme önerisinde bulunulmuştur. Anahtar Kelimeler: Sınır aşan birleşme, uygulanacak hukuk, şirket birleşmeleri, 2005/56/EC, AB hukuku. With the recent developments in international commercial law, cross-border mergers have been developed during the last few decades. Besides the advantages of merging with a company from a different country, there are also some difficulties especially about determining the applicable law. In European Union, Directive 2005/56/EC of the European Parliament and of the Council of 26 October 2005 on cross-border mergers of limited liability companies has been accepted to regulate this issue and harmonise the rules of substantive law of the member states. In Turkish law, despite the emphasize on the significance of the cross-border mergers at the preamble of Turkish Commercial Code, currently there is no codification about cross-border mergers. This study attempts to make a discussion about the applicable law to cross-border mergers from the perspective of Turkish law and a comparison between the regulations of European Union law and Turkish law. Yet, taking into consideration the EU-Turkey relations and the developments about the adaption of Turkish law to European Union law, the harmonization of rules about cross-border mergers must be inevitable. As the applicable law to cross-border mergers is topical and important subject for Turkish law, the study will also deal with the legislation proposal in accordance with European Union law. Key Words: merger, cross-border merger, applicable law, 2005/56/EC, EU law.
460545
Keywords: Avrupa Birliği hukuku; Birleşmeler; European Union law; Fusion d'entreprises; Intenational strategical mergers; International Law; International enterprises; International integrations; Mergers; Uluslararası Hukuk; Uluslararası bütünleşmeler; Uluslararası işletmeler; Uluslararası stratejik birleşmeler; Şirket birleşmeleri

Kurumsal yönetim ilkeleri bakımından halka açık anonim şirketlerde icrada görevli olmayan yönetim kurulu üyeleri - Küçükgüngör, Makbule Asli (Ankara Üniversitesi, 2017)
In publicly held companies where the shareholdership is differentiated from the control and the management of the company, the dispersed shareholding structure prevents the active involvement of the shareholders in the company management while the directors have the opportunity to act in their personal interests. The aforementioned conflict of interest between the shareholders and the directors in the management of the publicly held companies which has been identified as "Principle-Agent Problem" in economic literature has had substantial effect in modern company law. Accordingly, considerable work in the company law has been dedicated to the legal strategies developed to decrease the cost of monitoring directors for shareholders. One of the main corporate governance strategies that is developed to deal with the "Principle-Agent Problem" focuses on increasing the number and the effectiveness of the directors who are not involved in the managing activities of the company. The main principle of this legal strategy is the designing the structure of the board of directors on the basis of team spirit and mutual accountability. In that sense, non-management directors conduct their duties as directors without having management tasks in the company. As these directors work on a part time basis they are not fully depended to the company and in principle they receive symbolic amounts of remuneration. Under this incentive strategy it is accepted that the esteem and reputation that the non-management directors preserve in eye of the public are the main incentives that motivate them to monitor the managing directors. The corporate governance principles are designed as alternative to the rule based regulation approach in company law. The non-management directorship which is introduced as a corporate governance concept for solving the problem of conflict of interest between the shareholders and the directors is the focus area of this thesis. The thesis consists of five parts. In the first part of this study, the concept of corporate governance which is the source of non-management director concept and the conflict of intererest problem between the shareholders and the directors regarding the management of the publicly held companies have been introduced. In this regard, "Centralised Management" and "Principle-Agent Problem" are explained. Finally, based on the "Principle-Agent Problem" the legal theories that are developed to increase the effectiveness of the board of directors, the categorisation of those strategies that has been introduced and place of the non-management directors among those strategies are clarified. In the second part the emergence of the concept of non-management directorship system and the development of the mechanisms for increasing director independence are described and different forms of non-management directors in one-tier board structures are analysed. On this subject the legal designing of the concepts of independent and disinterested directorship which is developed in American law and non-executive directorship which is introduced in the British Law is analysed. In the third part, the concept of the supervisory directorship which corresponds to the non-management directorship in two-tier board system is examined. Forth part of the thesis focuses on the comparison of one-tier and two-tier board structures in application of the non-management directorship concept. Within this scope, it has been analysed whether there is a convergence in the functions of non-management directors in terms of supervision, strategy development and networking in the two types of board systems. Related to this analysis, the effectiveness of the non-management directors in one-tier and two-tier board systems and the role of the institutional investor regarding this effectiveness is evaluated. In recent years, depending on the inclination of convergence in different law systems, there has been an alignment effort in the European Union to have a single set of rules regarding the non-management directors. In this respect as a final focus point, in this part, the regulations of the European Union regarding the non-management directors are examined. The fifth part is dedicated to legal design of the independent directorship which is regulated under the non-management directorship concept in the Turkish law. Turkish Commercial Code is the general code that regulates all joint stock corporations including the publicly held ones. Therefore in order to explain the effects of Anglo-American approach on the administrative organ, the approach of the Turkish Commercial Code regarding the structure and functioning of the board of directors which are based on corporate governance principles are explained. Following that general introduction, the system change regarding the corporate governance principles in Turkey which consists of application of mandatory rules rather than "Comply or Explain" approach that is applicable to independent directors is explained. After that the independence criteria which are set for the independent directors under the capital market regulations for publicly held joint stock corporations and the role of independent directors in decision making mechanism are analysed. Finally, the structure and functioning of the board committees are evaluated by examining the functions of the independent board members.
482045
Keywords: Bağımsız idari otoriteler; Commercial law; Corporate governance; Halka açık ortaklıklar; Independent administrative authority; Kurumsal yönetim; Management; Members of the board directors; Principle; Public held companies; Representation; Ticaret hukuku; Vekalet; Yönetim; Yönetim kurulu üyeleri; İlke

Anonim ortaklık genel kurul toplantılarında pay sahibinin temsili - Tekten, Emel (Erciyes Üniversitesi, 2017)
Pay sahipleri genel kurula katılma maliyetlerinin fazla gelmesi, buna ayıracak zamanlarının olmaması veya sağlık sorunları gibi sebeplerle dolayı genel kurula katılmak istemeyebilir. Bunun sonucunda pay sahiplerinin şirketin işleyişine ve genel kurul kararlarına etki etme olasılıkları zayıfladığından; genel kurullarda, etkin ve iyi organize olmuş pay sahipleri gerçekte çoğunluk olmasalar da istedikleri kararların alınmasını sağlayabilmektedirler. Bu durum genel kurulda güç boşluğu sorununun doğmasına neden olmaktadır. Bu kapsamda anonim şirket genel kurulunda pay sahibinin temsilinin bu konudaki sorunları giderme de önemli bir rolü vardır. İşte tezimizin konusu, TTK ve SerPK çerçevesinde anonim şirket genel kurulunda pay sahibinin temsilidir. Bilindiği üzere 6102 sayılı TTK bir bütün olarak 01.07.2012 tarihinde yürürlüğe girmiş ve böylece elli yılı aşkın bir süredir uygulanan 6762 sayılı eTTK'yı yürürlükten kaldırmıştır. Yine 6362 sayılı SerPK 30.12.2012 tarihinde yürürlüğe girerek 2499 sayılı SerPK'yı yürürlükten kaldırmıştır. Bu yeni kanunlarda tez konumuzla ilgili olarak bir dizi değişiklikler yapılmış ve yenilikler getirilmiştir. Tez konusunun seçilmesindeki amaç, pay sahibinin temsiliyle ilgili olarak TTK ve SerPK mevzuatlarında getirilen yeni düzenlemelerin Yargıtay kararları, öğretideki görüşler ve mukayeseli hukuk ışığında değerlendirerek olası problemler karşısında çözüm önerileri getirip Türk Hukukuna katkı sağlamaktır. Bu tez çalışmasının ortaya konulması sırasında özellikle konuya kaynaklık eden İsviçre Hukuku ve literatüründen faydalanılmıştır. Konu, Türk Hukuku bakımından incelenirken İsviçre Hukukundan farklılıkları ve benzerlikleri ortaya konulmaya çalışılmıştır. Bunun dışında konumuzla ilgili olarak Alman, Amerikan, İngiliz ve Avrupa Birliği Hukuklarından da yararlanılmıştır. Yapılan değerlendirmeler sonucunda birçok sonuçlar elde edilmiştir. Ancak özellikle şunu belirtmeliyiz ki; halka açık anonim ortaklıklar düşünülerek getirilen TTK m. 428'de ifade edilen toplu temsilciler ile ilgili düzenleme, SerPK m. 30/4'te ve SPK II-30.1 sayılı Tebliğ m. 5/3 düzenlemeleri sebebiyle uygulanmayacaktır. Üstelik bu hükümler nedeniyle Türk Ticaret Kanunu ile Bazı Kanun ve Kanun Hükmünde Kararnamelerde Değişiklik Yapılmasına Dair Kanun Tasarısı Taslağı m. 12'de TTK m. 428, 430 ve 431 hükümlerinin yürürlükten kaldırılması öngörülmektedir. Getiriliş amacı geniş kitlelerin temsilini sağlamak olan bu hükümleri yürürlükten kaldırmak yerine, SerpK'nın ilgili hükümleri ile gerekli koordinasyon sağlanarak, bunların tüm ortaklıklar yönünden uygulanmasının yolu açılmalıdır. Anahtar Kelimeler: Anonim Ortaklık; Genel Kurul; Pay Sahibi; Temsil. Shareholders may refrain to join general assembly meetings due to the reasons like participation costs, lack of time and health issues. Since the possibility of the shareholders to have an impact on the functioning of the company and its general assembly gets weakened as a result of non-attendance, active and well-organized shareholder groups-despite the fact that they do not constitute the majority of the shareholders- may achieve their desired general assembly decisions. This particular issue causes an occurrence of a power gap in general assemblies. In this context, representation of the shareholders in the general assembly of the joint stock companies plays a role of utmost importance in eradicating such problems. Hence, the topic of my thesis is the representation of the shareholders in the general assembly of the joint stock companies within the legal framework of Turkish Commercial Code and Turkish Capital Market Code. As known, Turkish Commercial Code No. 6102 came into force in 01.07.2012, repealing former Turkish Commercial Code No. 6762 which was in force for more than fifty years. Also, Turkish Capital Market Code no. 6362 came into force in 30.12.2012, repealing former Turkish Capital Market Code no. 2449. There has been a series of amendments performed on those two codes concerning my thesis topic. My main goal on choosing this topic is to contribute to Turkish Law through assessing those amendments in the light of supreme court orders, scientific opinions and comparative law and to provide solutions to the existing and prospective problems. In preparation of this work, apart from Turkish Law, Swiss Law is highly referenced as it constitutes the main source of the issue. Therefore, while assessing the point, similarities and differences between Turkish and Swiss law is asserted. Besides, German Law, European Union Law, American Law and English law are also referenced for the sake of the proper assessment of the topic. As a consequence of made analyzes, a lot of conclusions are drawn. However, it is to be pointed out particularly that the regulations in Turkish Commercial Code No. 6102 article 428 which were provided considering open joint stock companies will not be applied because of Turkish Capital Market Code No. 2449 article 30/4 and the regulation of Turkish Capital Market Board no. II-30.1 article 5/3. Moreover, because of those provisions, repealing of the articles no. 428,430,431 of Turkish Commercial Code no. 6102 is at stake. Instead of repealing those provisions of Turkish Commercial Code no. 6102 -which aim at representation in a broader sense- establishing the coordination between those provision and related Turkish Capital Market Code provisions and enabling the application of those provisions on all sort of companies must be done. Keywords: Joint Stock Company, General Assembly, Shareholder, Representation
480444
Keywords: Actionnaires; Anonim ortaklıklar; Assemblée générale; Consumer right to representation; Genel kurul; Genel kurul kararları; General assembly; General assembly resdutions; Incorporated companies; Meetings; Pay sahipleri; Representation; Représentation; Shareholders; Temsil; Temsil edilme hakkı; Toplantılar; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Pay sahipleri sözleşmesinden doğan birlikte satma hakkı ve birlikte satışa zorlama hakkı - Yilmaz, Gülşah (Dokuz Eylül Üniversitesi, 2017)
Birlikte satma hakkı ve birlikte satışa zorlama hakkı pay sahipleri sözleşmesinde yer alan iki haktır. Bu hakların kaynağı Amerikan hukukudur. Bu haklar ülkemizde anonim şirket esas sözleşmelerinde sıklıkla yer almaktadır. Bu çalışmada Amerikan hukukundan gelen bu haklar Türk Ticaret Hukuku kuralları açısından incelenmiştir. İnceleme yöntemi ilk olarak hakların tanıtılması ikinci olarak ortaya çıkardığı hukukî ilişkinin niteliğinin tespiti ve son olarak hukukumuza ait yasal düzenlemeler karşısında ne derece geçerli kabul edilebileceğinin belirlenmesi şeklindedir. Çalışmada, hakların karşılaştırmalı hukuktaki yeri incelenmiştir. Bu kapsamda yabancı mahkeme kararları ve yasal düzenlemeler hakkında bilgi verilmiştir. Akabinde hakların hukukî niteliği ve haklardan doğan borçlar incelenmiştir. Son olarak hakların anonim ve limited şirket sözleşmelerinde yer alması durumunda meydana gelebilecek hukukî sorunlar tartışılmıştır. Bu kapsamda hakların yarattığı pay devir sınırlandırmasının anonim şirketler hukukunda yer alan kurallar karşısındaki durumu incelenmiştir. Ayrıca hakların limited şirketlerde pay devri ile ilgili düzenlemeler açısından geçerliliği tartışılmıştır. Anahtar Kelimeler: Birlikte Satma Hakkı, Birlikte Satışa Zorlama Hakkı, Pay Devrinin Sınırlandırılması, Pay Sahipleri Sözleşmesi, Anonim Şirket Esas Sözleşmesi. Tag along right and drag along right are two rights in shareholders' agreement. The source of these rights is American Law. These rights are frequently found in the articles of association of the joint stock company in our country. In this study, these rights coming from American law were examined in the terms of Turkish Commercial Law. The examination method is firstly the identification of the rights, secondly the determination of the nature of the legal relationship that emerges from the rights and finally the determination of the extent to which they can be regarded as valid under the legal regulations of our law. In the study, the position of the rights in comparative law were examined. In this context, information is given about the foreign court decisions and legal regulations. Then the legal nature of the rights and the obligations arising from the rights were examined. Finally, the legal issues that may arise in case of the rights are included in joint stock company and limited company contracts are discussed. In this context, the situation of the share transfer restrictions created by the rights against the rules in the corporation law has been examined. Furthermore, the validity of the rights in terms of the share transfer regulations in limited companies has been discussed. Keywords: Tag Along Right, Drag Along Right, Share Transfer Restriction, Shareholders' Agreement, Article Of Association.
486520
Keywords: Actionnaires; Anonim şirketler; Birlikte satma hakkı; Birlikte satışa zorlama hakkı; Birlikte vekalet; Drag along righ; Joint agency; Joint stock company; Pay devri; Pay sahipleri; Sale; Sales contracts; Sales methods; Satış; Satış sözleşmeleri; Satış yöntemleri; Shareholders; Tag along righ; Transfer of shares; Vente conjointe; Vente forcée